2009
DOI: 10.1122/1.3153551
|View full text |Cite
|
Sign up to set email alerts
|

Rheological, morphological and structural properties of PE/PA/nanoclay ternary blends: Effect of clay weight fraction

Abstract: The effect of an organically modified layered silicate on the rheological, morphological, and structural properties of immiscible polyethylene/polyamide ͑PE/PA͒ blends was investigated. The blends have been prepared for PA weight fractions ranging from 10 to 90% and at clay weight fractions from 1 to 6%. Scanning electron microscopy and transmission electron microscopy have been used to study the morphology and the structure of the blends. The dispersed phase size was shown to decrease with increasing clay con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 48 publications
6
62
0
1
Order By: Relevance
“…These phenomena can decrease the size of the PET/CNT phase in HDPE/PET/CNT composites when compared with the size of the PET phase in HDPE/PET blends. This was also observed in the literature for similar composite materials [26,27]. The difference in PET domain size in the blends and composites affects the tensile properties of the samples.…”
Section: Morphology Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…These phenomena can decrease the size of the PET/CNT phase in HDPE/PET/CNT composites when compared with the size of the PET phase in HDPE/PET blends. This was also observed in the literature for similar composite materials [26,27]. The difference in PET domain size in the blends and composites affects the tensile properties of the samples.…”
Section: Morphology Studiessupporting
confidence: 82%
“…A wide distribution of dispersed particle size is generally observed in the blends examined, due to the occurrence of coalescence phenomena of the minor phase during the melt mixing. The average diameter of PET and PET/CNT phases, which are etched away with trifluoro acetic acid, increases from 0.49 to 1.41 lm and 0.36 to 0.84 lm, respectively, as the PET content in the blend increases from 20 wt% to 30 wt%, due to droplet coalescence (Table 4) [25][26][27]. PET/CNT domain sizes in composite systems are smaller than the PET domain sizes in the blend systems (Table 4).…”
Section: Morphology Studiesmentioning
confidence: 99%
“…27 Moreover, the distribution of nanoparticles in binary blends is the subject of most new research in the field. [28][29][30][31] The location of nanofillers in each individual phase of the blends or at the interface can influence the final properties in different ways. Ashabi et al 29 showed by means of XRD, TEM and SEM measurements that in the blend of PA6 with SAN and ABS, the organoclay mostly localizes in the PA phase.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of a PA matrix, nanoclays are located in both the PA phase and at the interphase. 30 This work is motivated by the current researches in microcellular nanocomposite foams. 32,33 As a new approach, the location of nanofiller was tracked in the blend phases using AFM, DMTA and surface parameters and then the effect of nanoclay distribution on the final foam morphology was discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a la baja viscosidad en fundido de las mezclas PHBV/PLA, el mezclado en fundido a alta cizalla de estas mezclas no logra una buena dispersión de la fase dispersa, dada la competencia entre las fuerzas de cizallamiento (mecanismo de ruptura) y las fuerzas de tensión interfacial (mecanismo de coalescencia) [173,174].…”
Section: Mezclas De Polímerosunclassified